Success and complication rates after sacral neuromodulation for fecal incontinence and constipation: a single-center follow-up study - Widmann, Bernhard; Galata, Christian; Warschkow, René; Post, Stefan; Marti, Lukas (Journal of Neurogastroenterology and Motility, 2019)
Bernhard Widmann, Christian Galata, Rene Warschkow, Ulrich Beutner, Önder Ögredici, Franc H Hetzer, Bruno M Schmied, Stefan Post, and Lukas Marti. J Neurogastroenterol Motil 2019;25:159-70. https://doi.org/10.5056/jnm17106
Gesehen am 05.06.2019